Secrets Of Achieving Easy Performance On The Trombone (Based On The Pedagogical Experiences Of B. Fayziev) - Baxodir Abduraxmonovich Fayziev (Euro Asian Journal Publishing, 2024)
Interest in playing the trombone seems to have waned somewhat recently, but the flow of applicants entering the institute shows that this conclusion is incorrect. Because there are many students who want to learn this instrument. New students entering the institute will certainly have their shortcomings. In particular: problems with posture, airway, embouchure and tongue technique (attack) are clearly visible. How to solve these problems? In the next article, we will reflect on this topic and give advice on how to achieve an easier implementation of these problems.
Keywords: trombone; performance; body